Implementation of the Triple Helix Model in Increasing Economic Opportunities for Waste Management in Pangkalpinang City - Edih Mulyadi; Devi Valeriani; Eka Fitriyanti (Universitas Bangka Belitung, 2024)
This research reviews waste management problems in Pangkalpinang City, Indonesia, which is facing increasing waste volumes and suboptimal management. In an effort to overcome this problem, research uses a collaborative Triple Helix Model approach involving government, industry and universities. By combining the resources and competencies of these three parties, the research aims to develop a more effective and sustainable waste management model in Pangkalpinang. Through analysis of involvement and collaboration between government, industry and universities, this research explores the potential of the Triple Helix approach in overcoming waste management problems in the city. The research results show that the implementation of the Triple Helix Model has had a positive impact on waste management in Pangkalpinang City with various programs and initiatives that have been implemented. Recommendations for waste recycling programs are prioritized as an effective solution in maintaining environmental sustainability and creating new economic opportunities. However, there are still challenges such as lack of public awareness, limited resources, and technical obstacles that need to be overcome. By continuing effective collaboration between government, industry, academics and the community, it is hoped that waste management can continue to be improved and support sustainable development in Pangkalpinang City.